Business driven information systems - Baltzan, Paige (McGraw-Hill Irwin, 2008)
Business Driven Information Systems (also known as BDIS) discusses business initiatives first and then how technology supports those initiatives. The premise for this unique approach is that business initiatives drive technology decisions in a corporation. Every discussion first addresses the business needs and then addresses the technology that supports those needs. This text provides the foundation that will enable students to achieve excellence in business, whether they major in operations management, manufacturing, sales, marketing, etc. BDIS is designed to give students the ability to understand how information technology can be a point of strength for an organization